Antigenic pattern of the pig aortic valve and its simplification by culture and transplantation (Revista Española de Fisiología, 1973)
The antigenicity of the pig aortic valve was studied by immunoelectrophoresis on the valves before and after storage in a growth culture medium, and before and after grafting into dogs.Nine precipitation bands were detected in the fresh pig aortic valve. When the valve was cultured in a growth medium for five days, six bands were found. When the cultured valve was transplanted into the dog only three bands were detected. It seems therefore that when pig aortic valve is cultured and xenotransplanted an antigenic simplification occurs.